Chartergellus golfitensis West-Eberhard: A new species of Neotropical swarm-founding wasp (Hymenoptera: Vespidae, Polistinae) with notes on the taxonomy of Chartergellus zonatus Spinola - West-Eberhard, Mary Jane; Carpenter, James M.; Gelin, Luiz Fernando F. [UNESP]; Noll, Fernando B. [UNESP] (My University, 2010)
Chartergellus golfitensis West-Eberhard new species, is described from Central America and compared with C. zonatus Spinola, a species heretofore inadequately described.
Keywords: Hymenoptera; Polistinae; Vespidae